Relationship between Serum IgE and Intestinal Parasites - M Jalalian; M Rezaiian; EB Kia; J Massoud; M Mahdavi; MB Rokni (Tehran University of Medical Sciences, 2004)
Intestinal parasitosis has been a major public health problem in Iran. It is necessary to evaluate an up-date data in this regard to be used by local authorities. Serum IgE determinations and coproparasitological analyses were conducted on 1200 individuals in city of Ghaemshahr, Mazandaran province, northern Iran. A total of 1200 subjects were taken stool samples for three days consecutively. Two hundred and ninety seven cases (24.7%0) were positive for parasitic diseases. The age group of 8-15 years old encompassed the highest rate of infection which showed a significant difference with the other groups (P< 0.01). No significant difference was detected between males and females as to the rate of infection based on the Chi-squared test (14.2% vs. 10.6%), but a significant difference was seen between infection rate and cases education (P<0.01). An about 5-fold elevation in serum IgE level was demonstrated. Intervention programs including health education and environmental sanitation are recommended.